LekCheck: A Prospective Study to Identify Perioperative Modifiable Risk Factors for Anastomotic Leakage in Colorectal Surgery. Issue 1 (3rd January 2022) - Huisman, Daitlin E.; Reudink, Muriël; van Rooijen, Stefanus J.; Bootsma, Boukje T.; van de Brug, Tim; Stens, Jurre; Bleeker, Wim; Stassen, Laurents P. S.; Jongen, Audrey; Feo, Carlo V.; Targa, Simone; Komen, Niels; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To assess potentially modifiable perioperative risk factors for anastomotic leakage in adult patients undergoing colorectal surgery. Summary Background Data: Colorectal anastomotic leakage (CAL) is the single most important denominator of postoperative outcome after colorectal surgery. To lower the risk of CAL, the current research focused on the association of potentially modifiable risk factors, both surgical and anesthesiological. Methods: A consecutive series of adult patients undergoing colorectal surgery with primary anastomosis was enrolled from January 2016 to December 2018. Fourteen hospitals in Europe and Australia prospectively collected perioperative data by carrying out the LekCheck, a short checklist carried out in the operating theater as a time-out procedure just prior to the creation of the anastomosis to check perioperative values on 1) general condition 2) local perfusion and oxygenation, 3) contamination, and 4) surgery related factors. Univariate and multivariate logistic regression analysis were performed to identify perioperative potentially modifiable risk factors for CAL. Results: There were 1562 patients included in this study. CAL was reported in 132 (8.5%) patients. Low preoperative hemoglobin (OR 5.40, P < 0.001), contamination of the operative field (OR 2.98, P < 0.001), hyperglycemia (OR 2.80, P = 0.003), duration of surgery of more than 3 hours (OR 1.86, P = 0.010), administration of vasopressors (OR 1.80, P = 0.010), inadequate timing of preoperative antibiotic prophylaxis (OR 1.62, P = 0.047), and application of epidural analgesia (OR, 1.81, P = 0. 014) were all associated with CAL. Conclusions: This study identified 7 perioperative potentially modifiable risk factors for CAL. The results enable the development of a multimodal and multidisciplinary strategy to create an optimal perioperative condition to finally lower CAL rates.